ETIKA POLITIK PEMENUHAN HAK ASASI MANUSIA DALAM ERA GLOBALISASI - Nurdin, M. Nurwandi; Razak, Muhammad Rais Rahmat (Jurusan Ilmu Pemerintahan Universitas Palanfka Raya, 2023)
Political ethics plays an important role in realizing human rights in the context of globalization. Globalization has connected countries and communities around the world and created opportunities to increase access to and protection of human rights. However, this phenomenon also raises ethical challenges in a complex global political landscape, and this article examines the role of political ethics in ensuring the realization of human rights in globalization. First, we discuss the principles of political ethics that should guide political policy and action in the context of globalization. It also analyzes various ethical issues that arise in human rights activities, such as cultural domination, economic inequality, and environmental problems. In conclusion, this article emphasizes the importance of international cooperation based on sound political ethics to face these challenges and facilitate the realization of human rights in the era of globalization.